2019
DOI: 10.5603/pjnns.a2019.0056
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker concordance between molecular stereotactic biopsy and open surgical specimens in gliomas

Abstract: Aims. To compare 1p/19q codeletion, MGMT promoter methylation, and IDH mutation status in stereotactic biopsy and open craniotomy specimens. clinical rationale. The latest WHO classification of gliomas requires assessment of the expression of molecular markers. Samples can be obtained for molecular assays via open craniotomy or molecular stereotactic biopsy (MSB). However, there is uncertainty as to whether MSB is representative of the entire tumour, and therefore how reliable it is for treatment planning.Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…When microsurgical excision is not feasible, stereotactic biopsy should be performed due to its safeness, effectiveness, and high concordance with open surgical specimens in acquiring diagnostic material. In the era of the WHO CNS5 2021 classification, collecting representative samples for histological and molecular investigations is essential [ 19 , 20 ]. Next, the IDH gene status assessment seems to be a crucial step in the management of a patient with astrocytoma.…”
Section: Discussionmentioning
confidence: 99%
“…When microsurgical excision is not feasible, stereotactic biopsy should be performed due to its safeness, effectiveness, and high concordance with open surgical specimens in acquiring diagnostic material. In the era of the WHO CNS5 2021 classification, collecting representative samples for histological and molecular investigations is essential [ 19 , 20 ]. Next, the IDH gene status assessment seems to be a crucial step in the management of a patient with astrocytoma.…”
Section: Discussionmentioning
confidence: 99%
“…Stereotactic biopsies for intrinsic brainstem lesions were as safe and effective as biopsy of lesions in the supratentorial compartment [ 12 ]. Moreover, we previously reported that the initial histological findings obtained by stereotactic biopsy were the same as for open surgery [ 26 ]. Ramakonar et al argued that even if the biopsy material was non-diagnostic in histological evaluations, molecular testing should be performed, since mutations in IDH1 and TERT may still be detected [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…[2,12,16,21,22,23,27,34,52,51,53] is result may be related to the relatively great number of samples (n = 12) collected during the procedure, contrarily to others who usually harvest four samples or less. [3,4,7,[10][11][12][13]18,[20][21][22][23][24]27] On the other hand, the collection of a greater number of samples may theoretically increase the chance of bleeding complications. However, intralesional hemorrhage occurred in a single occasion in this series (3.4%), which fortunately was asymptomatic and did not produce any mass effect (diameter = 10 mm).…”
Section: Discussionmentioning
confidence: 99%